2018
DOI: 10.1128/mcb.00154-18
|View full text |Cite
|
Sign up to set email alerts
|

The VCP-UBXN1 Complex Mediates Triage of Ubiquitylated Cytosolic Proteins Bound to the BAG6 Complex

Abstract: A balance between protein synthesis and degradation is necessary to maintain cellular homeostasis. Failure to triage aberrant proteins may result in their accumulation and aggregation in the cytosol. The VCP-BAG6 complex facilitates a wide variety of ubiquitin-mediated quality control events at the ER; both prior to ER translocation as well as during ER associated degradation (ERAD). Yet, how ubiquitylated clients associated with BAG6 are recognized by VCP for proteasomal degradation is presently unknown. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 30 publications
1
46
1
Order By: Relevance
“…In this context, it should be interesting to note that RNF126 has a role in membrane protein sorting in HeLa cells . Recently, it was reported that some BAG6 client proteins are degraded by the UBXN1‐mediated pathway . Therefore, it might be interesting to examine this possibility with Rab8a (T22N) as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it should be interesting to note that RNF126 has a role in membrane protein sorting in HeLa cells . Recently, it was reported that some BAG6 client proteins are degraded by the UBXN1‐mediated pathway . Therefore, it might be interesting to examine this possibility with Rab8a (T22N) as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 72 autosomal dominant mutations have been discovered in this gene, more than 30 of which are reported in ALS or FTD cases (including behavioral FTD, semantic dementia, and progressive non-fluent aphasia) (Al-Obeidi et al, 2018;Saracino et al, 2018;Bastola et al, 2019). Many of the reported VCP mutations are located on exon five within the N-terminal CDC48 domain, which is involved in ubiquitinbinding, meaning that mutations in this region may negatively affect the ubiquitin protein degradation pathway (Ganji et al, 2018;Twomey et al, 2019).…”
Section: Valosin Containing Protein (Vcp)mentioning
confidence: 99%
“…Like other chaperones, it plays an important role in triaging its substrates. While its folding capability is minor, BAG-6 can act as a holdase and prevent aggregation of TA transmembrane proteins [210], and keep ERAD-substrates soluble before further processing by p97 [212,217].…”
Section: Degradation Through Bag-6mentioning
confidence: 99%